PERADILAN IN ABSENSIA DALAM KAITANNYA DENGAN PERLINDUNGAN HAK ASASI TERDAKWA - Novita, Rini (Universitas Islam Sumatera Utara, 2024)
stated in Article 1 sub 15 of the Criminal Procedure Code, that the defendant is a suspect who is charged, examined and tried in court. The principle of the defendant's presence in a criminal case is based on the defendant's human rights as a human being who has the right to defend himself and defend his rights to freedom, property or honor. In absentia justice, there are two mutually contradictory interests, namely the interests of society or the state and the interests of the suspect/accused on the other hand, so that the issue of in absentia justice is a difficult and complex problem, as well as an actual problem to be discussed. The government and legal practitioners in general should pay more serious attention to efforts to develop a method or system that can bring these two conflicting interests into a situation where the interests of both are truly taken into account. According to the Criminal Procedure Code, when examining criminal cases, the District Court must hear the defendant's own statement in order to give the defendant an opportunity to defend himself. In certain criminal offenses, there is the possibility of being tried outside the presence of the defendant (in absentia) provided that he has been summoned twice in a row to legally fail to appear at the court hearing, the court has the authority to try him outside the presence of the defendant. Keywords: Justice, In Absence of the Human Rights of the Defendant